Il Caso di Veio: Nuove scoperte archeologiche con APR - Baglione, Zaira (GEOmedia, 2015)
Etruscan settlements outside Rome identified by the use of fixed wing UAV FlyGeo24Mpx. Prof. Giuseppe Ceraudo from University of Salento and Gabriele Santiccioli of Fly-Top explain the results of the mission in the Veio Park as proof of the reliability of the UAV technology at the service of the archeology.